Anti-Wrinkle Efficacy of Edible Bird’s Nest Extract: A Randomized, Double-Blind, Placebo-Controlled, Comparative Study - Kim, Hyung Mook; Lee, Yong Moon; Kim, Ee Hwa; Eun, Sang Won; Sung, Hyun Kyung; Ko, Heung; Youn, Sang Jun; Choi, Yong; Yamada, Wakana; Shin, Seon Mi (Frontiers in Pharmacology, 2022)
This study aimed to evaluate the functional improvement and safety of skin health, such as wrinkles, elasticity, moisturizing, and whitening, following the consumption of ‘bird nest extract’ for 12 weeks by women. This single-center, double-blinded, parallel-group, placebo-controlled study included women aged from 40 to <60 years. Our primary purpose was to assess improvement in skin wrinkles, elasticity, and moisture after 12 weeks using SV700, cutometer, and corneometer, respectively, compared with those at baseline. Our secondary purpose was to evaluate changes in skin wrinkle, elasticity, and moisture at 4 and 8 weeks from baseline using the aforementioned equipment and those in the amount of transdermal water loss and melanin and erythema index using tewameter and mexameter, respectively. Experts performed the visual evaluation of skin wrinkles at 4, 8, and 12 weeks from the baseline. The participants were randomly allocated in a 1:1 ratio into the bird nest extract or placebo group, where they consumed 100 mg of the extract or placebo, respectively, daily for 12 weeks. The outcomes were measured at every visit. In this study, upon comparing changes in skin elasticity value between the two intake groups at 12 weeks of ingestion, those in the bird nest extract group decreased significantly, compared with the placebo group. Adverse reactions were absent in both groups. In case of laboratory test results, changes before and after the ingestion of the extract were within the normal range, thus indicating no clinically significant difference. The bird nest extract was effective in improving skin wrinkles. Moreover, it was beneficial for skin health and can be used as a skin nutritional supplements. Compared with the placebo, the bird nest extract was identified as safe.